ANALYSIS OF CONSUMER ONLINE IMPULSIVE BUYING BEHAVIOUR IN MANADO - Lalelung, Marcela E.; Pangemanan, Sifrid S. (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Nowadays business E-commerce has growing rapidly in Indonesia, and through the development of technology there is a concept as a new paradigm which is online shopping, and online shopping become the place that people can visit anytime to buy a product, and there are many factors that stimulated people to do impulsive buying. Nowadays the consumer buying behaviour which is impulse buying has becoming such a part of every person’s lifestyle that they do not realize or they are not even aware that they are doing it at times. This study aims to analyze the factors that stimulated people to do impulsive buying. This research uses Qualitative Method with In-depth Interview, in order to know more detail about the factors that stimulated people to do impulsive buying. The result of the research shows that internal and external factors have significant influence to the behaviour of the consumer when buying impulsively through online shops and based from all the informant the factors that dominant stimulated people to do impulsive buying is internal factors. The suggestion it is better to online shopping mantain their quality and for consumer it is better to realize what factors that stimulated them to do impulse buying.Keywords: impulse buying, buying behaviour, online shopping, internal factors, external factors.